(3EOGQI GdYbd (B=s Instant Brainpower - (3cdjL, HQjGfs; (3OGQ GdaGQhbs ((3GdbGgQIs (3OGQ GdaGQhb ddfTQ hGdJhRjYs, 2003)
(3EOGQI GdYbd Hbde HQGjGf cdjL (B... "(3GdEHOGY (B- (3GdeYQaI (B- (3JMSjf WQb GdJacjQ(B" (3Jbhd GdMceI GdbOjeI Cf eG jge gh eG JYQag hdjS ef JYQag(B. (3dcf aj gPg GdCjGe, JYJHQ GdeYQaI hGSJNOGegG GdEHOGYj geG CSGSG GdfLGM(B. (3eG eOi caGAJc aj Jchjf eNRf ef GdeYQaI dJSJNOeg CaVd GSJNOGe? gd jecf dPGcQJc Cf Jchf CaVd? agPG GdJOQjH GdPj fbOeg ddYbd SjSGYOc Ydi GdEKQGA ef egGQGJc GdYbdjI hJMSjfgG hRjGOI SQYI GdJacjQ(B. (3jYJHQ cJGH (B"(3EOGQI GdYbd(B" (3ef GdcJH GdJj JJSe HSghdI GdGSJNOGe MjK jeJdF HGdcKjQ ef GdJOQjHGJ GdJj JSGYOc Ydi GdGSJaGOI ef Ybdc CbUi GSJaGOI eecfI(B. (3agh jRNQ HGdYOjO ef CSGdjH GdJacjQ GdHSjWI GdJj JSGYOc Ydi GdYKhQ Ydi eRjO ef GdCacGQ hGdMdhd, YdGhI Ydi Cfg jYQV eG jbQH ef WQjbI Jecfc ef JhSjY fWGb JacjQc hPgfc hbOQGJc(B. (3jJVef gPG GdcJGH GdehVhYGJ GdJGdjI(B: (3EKQGA WQjbI EOGQI GdeYQaI hGdbOQI Ydi Yed GdGJUGdGJ Cf JLYd PGcQJc TjA fGaY PG bjeI RjGOI bOQJc Ydi GdJacjQ GdEjLGHj GdJacjQ aj WQb LOjOI heMGhdI EjLGO Mdhd EHOGYjI jMJhj gPG GdcJGH Ydi GdCacGQ GdJj JSGYOc Ydi JMSjf WGbJc GdEHOGYjI hMSf GSJNOGegG, YdGhI Ydi Cfg jMJhj Ydi Jbjje aj fgGjI cd JOQjH hGdJj JTjQ Edi eOi caGAI cd JOQjH hOhQg aj JMSjf GdeYQaI hGdPGcQI hGdEHOGY, YdGhI Ydi ebOGQ GdeJYI GdJj SJMbbgG ef cd JOQjH(B. (3dG JacQ aj JMSjf bOQGJc GdacQjI GdYbdjI, dcf be HPdc Ydi GdahQs
(3eJhaQ efg GdWHYI GdSGOjI HecJHI eUQ GdYGeI aQY GdRGhjI GdMeQGAs
1
Keywords: (3GdEOQGcs; (3GdJacjQs; (3GdYbds